Mechanisms of Tadabbur (contemplating) the Holy Qur’an for Non-Arabs - Mohamed Abdelmonem elSayed Khalil; Yasir bin Ismail Radi; Abdulwahab Abdulaziz Kassem al-Haddad ((الطموحات ) EL-THUMUHAT, 2022)
Abstract The importance of contemplating the Holy Quran for a Muslim's belief and its positive impact on the course of his life, worship, and dealings is not hidden from any rational person. Hence, this study, which aimed to help in providing mechanisms and means that help in contemplating the words and meanings of the Noble Qur’an for our Non-Arabs speaking brothers, responds at the same time to the definition of contemplation and the importance of contemplation of the Noble Qur’an, which brings benefit and goodness to the life and worship of a Muslim. Keywords: The Holy Quran - Tadabbur – Non-Arabs – Mechanisms.